The Fifth Hutton Symposium on the Origin of Granites and Related Rocks 2004
DOI: 10.1130/0-8137-2389-2.319
|View full text |Cite
|
Sign up to set email alerts
|

Crustal control on the redox state of granitoid magmas: tectonic implications from the granitoid and metallogenic provinces in the circum-Japan Sea Region

Abstract: Felsic magmatism has occurred over a large region of East Asia since Jurassic times and has provided important mineral resources such as tin, tungsten, base metals and gold. The circum-Japan Sea region preserves various geological records of active continental margins, including Jurassic to Early Tertiary magmatic arcs and subduction zones and pre-Jurassic continental basements, which were separated by the opening of the Japan Sea during the Miocene. The felsic magmatism in this region shows a wide variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 29 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…The reduced character of the ilmenite-series intrusions is generally considered to reflect a reduced crustal source, principally the carbonaceous sedimentary component of the late Paleozoic, Jurassic, and Cretaceous-Paleogene accretionary complexes and their high-P/T metamorphic equivalents that underlie much of Japan (Ishihara, 1977(Ishihara, , 1981(Ishihara, , 2004Sato et al, 2004;Sato, 2012;Fig. 2).…”
Section: Redox Statementioning
confidence: 99%
See 2 more Smart Citations
“…The reduced character of the ilmenite-series intrusions is generally considered to reflect a reduced crustal source, principally the carbonaceous sedimentary component of the late Paleozoic, Jurassic, and Cretaceous-Paleogene accretionary complexes and their high-P/T metamorphic equivalents that underlie much of Japan (Ishihara, 1977(Ishihara, , 1981(Ishihara, , 2004Sato et al, 2004;Sato, 2012;Fig. 2).…”
Section: Redox Statementioning
confidence: 99%
“…Porphyry Cu deposits worldwide are hosted by magnetite-series intrusions of upper mantle and/or lower-crustal provenance, which are thought to attain their oxidized states by contributions of volatiles, SO 4 2− , and Fe 3+ from subducted oceanic slabs (Ishihara, 1977(Ishihara, , 1981Mungall, 2002;Kelley & Cottrell, 2009). The original oxidized states of the magmas are variably retained, depending on rate of ascent through the crust, whether the latter was originally oxidized or underwent some degree of oxidation during earlier magnetite-series magmatism (Sato et al, 2004;Sato, 2012), and potentially other factors (e.g., magnetite fractionation; Jenner et al, 2010). It is important to stress that oxidized melts and fluids are a fundamental requirement for effective Cu transport through the mantle and crust, which also maximises their S (as SO 4 2− )-carrying capacity (e.g., Richards, 2015).…”
Section: Redox Statementioning
confidence: 99%
See 1 more Smart Citation
“…In order to emphasize this aspect, the ilmenite/magnetite-series can also be named the reduced/oxidized types (e.g. Sato et al, 1992Sato et al, , 2004aSato, 2003). The reduced/oxidized types are used in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The genesis of this contrast is considered to be a result of global geodynamic processes. Sato et al (2004aSato et al ( , 2006b and Sato (2006) suggested that repeated magmatism along a convergent margin of the North and South American continents for a long period could have produced oxidized-type granitoids due to the depletion of sedimentary carbon, an essential reducing agent, while sedimentary crusts could have been involved in magmatism in the Asian side in various stages during more complicated tectonic history than the monotonous convergent margin of the American side. However, this insight is to be reexamined through careful analyses of geotectonic information for individual regions.…”
Section: Introductionmentioning
confidence: 99%